2016
DOI: 10.1371/journal.pone.0156422
|View full text |Cite
|
Sign up to set email alerts
|

MGMT Promoter Methylation and BRAF V600E Mutations Are Helpful Markers to Discriminate Pleomorphic Xanthoastrocytoma from Giant Cell Glioblastoma

Abstract: Giant Cell Glioblastoma (gcGBM) and Pleomorphic Xanthoastrocytoma (PXA) are rare astroglial tumors of the central nervous system. Although they share certain histomorphological and immunohistochemical features, they are characterized by different clinical behavior and prognosis. Nevertheless, few cases remain uncertain, as their histomorphological hallmarks and immunophenotypes do correspond to the typical pattern neither of gcGBM nor PXA. Therefore, in addition to the routinely used diagnostic histochemical a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 39 publications
0
10
0
1
Order By: Relevance
“…Four gcGBM samples (40%) were positive for MGMT methylation as revealed by MSP. Similar prevalence of MGMT methylation was reported by Lohkamp et al . MGMT methylation was not associated with age, sex or overall survival.…”
Section: Resultsmentioning
confidence: 99%
“…Four gcGBM samples (40%) were positive for MGMT methylation as revealed by MSP. Similar prevalence of MGMT methylation was reported by Lohkamp et al . MGMT methylation was not associated with age, sex or overall survival.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, it was this immunohistochemical observation, along with the consistent failure of the tumors in this series to manifest labeling for IDH1 R132H or chromosome 1p/19q codeletion, despite their oligodendrogliomatous appearances, that prompted us to consider these as distinct from the infiltrating gliomas of later life and to initiate additional molecular studies. While the immunohistochemical labeling of some glioblastomas for CD34 is recognized [ 19 , 25 ], this phenomenon is generally foreign to infiltrating astrocytomas of lower grade and to neoplasms of the oligodendroglioma group [ 2 , 5 , 6 , 10 , 13 15 , 28 , 29 , 32 , 36 , 43 , 45 47 ]. Only one of the many studies that have examined CD34 expression in gliomas found tumoral (as opposed to endothelial) immunoreactivity in lesions classified as WHO grade II or III astrocytomas, oligodendrogliomas or oligoastrocytomas [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, several small series and case reports have suggested that the prognosis of GCG is significantly better than that observed for GBM (Akslen et al, 1988;Becker et al, 1967;Burger & Vollmer, 1980;Chang, Kuwana, Ito, Koike, & Kitamura, 2001;Deb, Sharma, Chander, Mahapatra, & Sarkar, 2006;Gullotta, Casentini, & Neumann, 1980;Klein, Molenkamp, Sorensen, & Roggendorf, 1998;Kroh, Matyja, Marchel, & Bojarski, 2004;Margetts & Kalyan-Raman, 1989;Sabel, Reifenberger, Weber, Reifenberger, & Schmitt, 2001;Shinojima et al, 2004). The development of GBG is highly related to mutations of the TP53 gene (Kleihues & Glioblastoma,) MGMT promoter methylation, mutations in the IDH1/2 genes, or BRAF mutations, which are actually used as diagnostic, prognostic, and predictive molecular markers in anaplastic glial tumors (Lohkamp et al, 2016).…”
mentioning
confidence: 99%